The effects of repeated days of intense training on intramuscular energy stores
On what's to do to replenish glycogen stores fully between workouts whwn training twice a day. The restoration of glycogen should be a daily procedure. Carbohydrate enhanced drinks before, during, and after practice, complex carbohydrate meals three times a day, and workloads that are terminated when energy no longer is available to fuel competition specific training stimuli are factors which must be included in the training regimen of swimmers.